KEDUDUKAN AKAL DALAM ISLAM: PERDEBATAN ANTARA MAZHAB RASIONAL DAN TRADISIONAL ISLAM - Reynaldi Adi Surya (Ushuluna: Jurnal Ilmu Ushuluddin, 2019)
Reason has an important and vital meaning in human life. It's not wrong if it says about what makes human survive and expand their culture along with their amazing civilization. in moslem, reason also recognized as one of god's greatest creation, but in moslem's intellectual tradition, scholars and highbrows argue about what mind actually means and the extent role of reason spiritually. Moslem philosophers and fuqaha ahl ra'y stick up with reason as the source of knowledge and references within life and religions problem, however hadith expert and the one who stick to literal tradition assume that mind's role is very limited in religions problem, some even think that reason is not permitted to play in religion realm. Up until this moment, classic debate about reason and human rational capability are still being debated, especially in religion realm. writer tried as much as possible to redescribe those controversy shortly in this article.